Kesiagaan Menghadapi Bencana Pandemi Covid-19 di Kantor Arsip Universitas Indonesia - Anggraeni, Novia; Mirmani, Anon (UI Scholars Hub, 2022)
The condition of restrictions on community activities due to the COVID-19 pandemic has forced the Archives Office at Universities to adjust archive services. COVID-19 disaster preparedness needs to be implemented within the University of Indonesia Archives Office. This study aims to identify the preparedness of the University of Indonesia Archives Office in dealing with the COVID-19 disaster and. This is qualitative research with case study method. The results show that the University of Indonesia Archives Office has responded to the COVID-19 pandemic situation by carrying out various preparedness efforts that are implemented in service activities and archive management. The obstacle faced by staff and leaders during the pandemic is establishing communication and interaction. Based on the results of the study, the suggestion from this research is that the University of Indonesia Archives Office needs to make a post-disaster recovery plan and look for efforts to establish effective communication during the pandemic between staff and leaders.